2017
DOI: 10.1128/mcb.00061-17
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Levels of Phosphorylated Mitogen-Activated Protein Kinase Kinase 1/2 Determined by Mortalin/HSPA9 and Protein Phosphatase 1 Alpha in KRAS and BRAF Tumor Cells

Abstract: Although deregulation of MEK/extracellular signal-regulated kinase (ERK) activity is a key feature in cancer, high-magnitude MEK/ERK activity can paradoxically induce growth inhibition. Therefore, additional mechanisms may exist to modulate MEK/ERK activity in favor of tumor cell proliferation. We previously reported that mortalin/HSPA9 can facilitate proliferation of certain KRAS and BRAF tumor cells by modulating MEK/ERK activity. In this study, we demonstrated that mortalin can regulate MEK/ERK activity via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Pancreatic cancer (Panc-1) cells have previously been shown to (i) abundantly express mortalin, VEGF and MMP [49][50][51]; (ii) harbor a high number of oncogenic mutations in KRAS, TP53, CDKN2A/p16 and SMAD4/DPC4 [52]; (iii) possess strong migratory and adhesive abilities [53] and (iv) easily cluster and difficultly differentiate into their functional phenotypes [54]. Thus, we chose to examine the regulation of EMT by the TEG derivatives in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer (Panc-1) cells have previously been shown to (i) abundantly express mortalin, VEGF and MMP [49][50][51]; (ii) harbor a high number of oncogenic mutations in KRAS, TP53, CDKN2A/p16 and SMAD4/DPC4 [52]; (iii) possess strong migratory and adhesive abilities [53] and (iv) easily cluster and difficultly differentiate into their functional phenotypes [54]. Thus, we chose to examine the regulation of EMT by the TEG derivatives in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mortalin also affected Ras activity through its interaction with mevalonate pyrophosphate decarboxylase, an enzyme that biochemically modifies Ras [24]. Although the exact location for the regulation is yet unclear, we have recently demonstrated that mortalin negatively regulates the activity of the Raf/MEK/ERK pathway by promoting the physical interaction between protein phosphatase 1 alpha and MEK1/2 [25]. Of note, this ability of mortalin to modulate the Raf/MEK/ERK pathway was important for B-Raf V600E melanoma and K-Ras G12V colon carcinoma cells to bypass the cytostatic effects associated with high MEK/ERK activity [12].…”
Section: Discussionmentioning
confidence: 99%
“…A375 cells were infected with the lentiviral pLKO.1-shACO2 (TRCN0000056561, Dharmacon, Lafayette, CO, USA) to suppress aconitase-2 or the control pLKO.1 for 3 or 6 days prior to EPR. Lentivirus production and infection procedures were previously described [ 27 , 28 , 29 ]. Cells were treated with 10 µM chromate (Sigma, St. Louis, MO, USA) in HBSS (Invitrogen) in a CO 2 incubator at 37 °C for 30 min and were harvested using cell scrapers.…”
Section: Methodsmentioning
confidence: 99%